Mapping where ecologists work: biases in the global distribution of terrestrial ecological observations. Issue 4 (30th March 2012) - Martin, Laura J; Blossey, Bernd; Ellis, Erle
Abstract : Although the geographical context of ecological observations shapes ecological theory, the global distribution of ecological studies has never been analyzed. Here, we document the global distribution and context (protected status, biome, anthrome, and net primary productivity) of 2573 terrestrial study sites reported in recent publications (2004–2009) of 10 highly cited ecology journals. We find evidence of several geographical biases, including overrepresentation of protected areas, temperate deciduous woodlands, and wealthy countries. Even within densely settled or agricultural regions, ecologists tend to study "natural" fragments. Such biases in trendsetting journals may limit the scalability of ecological theory and hinder conservation efforts in the 75% of the terrestrial world where humans live and work.